Gestão de projetos no Terceiro Setor: avaliação de projetos sociais na Economia Solidária - Cilento, Ivo (2019)
This study explores the management of social projects as a phenomenon at local level. In the aim of that, it is proposed to answer the question of how the existing body of knowledge in project management applies to the social projects? The research path goes through understand how social projects are actually conducted, as well as their specificities and challenges. In this intent, the work uses the Project Management Body of Knowledge (PMBOK Guide) as the reference for analysis. For the empirical effort, the social solidarity projects in the field of Solidary Economy were chosen, within the general concept of Third Sector. In particular, the focus of the study is how project management processes operates in the substantive logic of solidary ventures. The work begins with three systematic literature reviews covering the concept of project, the project management as discipline, project management in the third sector, the conceptualization of the third sector and the origin and development of the solidary economy, among others. In methodological terms, the research is set as a basic qualitative research, where data from past project reports and interviews with five organizations were analyzed using the Constant Comparative Method to understand the investigated reality. This course allowed to present a concept for social projects and to identify their connection with the public policies. By means of a code mapping in a matrix based on the PMBOK, the research was able to define, for instance, a large use of stakeholders and integration management, in contrast to a slight use of the purchase management. It recognizes in the planning of risk and schedule management the greater opportunities to use the PMBOK in advantage of a less reactive action in face of the challenges of this context. The results also indicate how these projects would benefit from the PMBOK for expanding the options of documents, tools, techniques and life cycle models. Emerging themes also indicates where social solidarity projects can contribute to the existing knowledge, such as in the sustainability aspect and in network acting. The latter was recognized as a social and collaborative capacity. Finally, the research still recognizes points where social solidarity projects touch the agile project management approach.